2017
DOI: 10.1108/ijchm-04-2016-0216
|View full text |Cite
|
Sign up to set email alerts
|

Assessing servicescape of cruise tourism: the perception of Chinese tourists

Abstract: Purpose This study aims to develop a comprehensive framework for assessing servicescape of cruise tourism and provides practical suggestions to improve the perception of Chinese tourists toward cruise servicescape. Design/methodology/approach A multistage mixed-method design was used in the sequence of in-depth interviews (n = 18), expert panel (n = 5), on-site survey (n = 317) and online survey (n = 300). Grounded theory, exploratory factor analysis and confirmatory factor analysis were used to assess cruis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 46 publications
(66 reference statements)
1
70
2
1
Order By: Relevance
“…Two levels of data We applied EFA using maximum likelihood estimation (MLE) with oblimin rotation. Since it had become elusive to which servicescape factors remained relevant in the context of public hospitals, we concurred with the idea of exploring the possible antecedents, which was apparent in the studies of Lyu, Hu, Hung and Mao (2017). MLE is our choice of factor extraction because of two reasons; 1) MLE can provide consistent results across models; 2) MLE has remained the preferred estimator across settings (Byrne, 2010).…”
Section: Data Collectionmentioning
confidence: 63%
“…Two levels of data We applied EFA using maximum likelihood estimation (MLE) with oblimin rotation. Since it had become elusive to which servicescape factors remained relevant in the context of public hospitals, we concurred with the idea of exploring the possible antecedents, which was apparent in the studies of Lyu, Hu, Hung and Mao (2017). MLE is our choice of factor extraction because of two reasons; 1) MLE can provide consistent results across models; 2) MLE has remained the preferred estimator across settings (Byrne, 2010).…”
Section: Data Collectionmentioning
confidence: 63%
“…(Nilsson & Ballantyne, 2014),, (Ardley & Chen, 2017). There is one that uses a mixed quantitative and qualitative method (Lyu et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Layout relates to the positioning of furniture and various equipment in the area used by the customer, taking into account how the area is in, the concept of decoration, how the color and wall arrangement and the quality of the material; spatial layout and functionality (Nathaniel D. . Service-scape as a physical display is indeed very important in environmental governance and elements related to infrastructure, objects; but besides that there are other things that are no less important, namely atmosphere, hospitality, communication, culture, value, provisions, natural law (Park et al, 2019),atmosphere such as customer satisfaction, experience, consumption; Social factors, such as the behavior of others in the environmental service-scape can also influence customer satisfaction, attitudes and other behaviors (Dassanayake & Senevirathne, 2018), (Lyu et al, 2017). The full list of research themes, contexts, methodologies, theories used and research locations is described as shown in Appendix 1.…”
Section: Proposed Upcoming Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, despite the plethora of recent studies on cruise tourism (Andriotis & Agiomirgianakis, ; Han, Lee, & Hwang, ; Juan & Chen, ), empirical evidence on the relation between SWB and cruise travel remains scant and weak, not to mention the absence of such literature focusing on Chinese tourists. Considering the substantial cultural and social‐economic differences between China and Western societies and China's huge potential for the cruise market (Lu, Hu, Hung, & Mao, in press), research on Chinese cruise tourism appears to be highly promising. Therefore, the main focus of this research is to explore the psychological mechanism through which cruise experience affects SWB over time.…”
Section: Introductionmentioning
confidence: 99%